Formation of Plasma Around a Small Meteoroid: Electrostatic Simulations. Issue 5 (29th May 2019) - Sugar, G.; Oppenheim, M. M.; Dimant, Y. S.; Close, S.
Abstract: Obtaining meteoroid mass from head echo radar cross section depends on the assumed plasma density distribution around the meteoroid. An analytical model presented in Dimant and Oppenheim (2017a, https://doi.org/10.1002/2017JA023960 ; 2017b, https://doi.org/10.1002/2017JA023963 ) and simulation results presented in Sugar et al. (2018, https://doi.org/10.1002/2018JA025265 ) suggest the plasma density distribution is significantly different than the spherically symmetric Gaussian distribution used to calculate meteoroid masses in many previous studies. However, these analytical and simulation results ignored the effects of electric and magnetic fields and assumed quasi‐neutrality. This paper presents results from the first particle‐in‐cell simulations of head echo plasma that include electric and magnetic fields. The simulations show that the fields change the ion density distribution by less than ∼2% in the meteor head echo region, but the electron density distribution changes by up to tens of percent depending on the location, electron energies, and magnetic field orientation with respect to the meteoroid path. Key Points: We model the plasma density formed around a small ablating meteoroid with particle‐in‐cell simulations The simulations relax assumptions used in previous solutions by including charged particle dynamics as well as electric and magnetic fields Electric and magnetic fields have little effect on the ion distribution but do impact the electron distribution